Genetic diversity of Plasmodium falciparum isolated from Yemen based on the genes of merozoite surface proteins (MSP) 1 and 2 - Mahdy, M.; Al-Abd, N.; Al-Mekhlafi, A.; Abdul-Majed, N.; Al-Mekhlafi, H.; Fong, Mun Yik (Wiley, 2011)
Background: Malaria is still a public health problem in Malaysia especially in the interior parts of Peninsular Malaysia and the states of Sabah and Sarawak (East Malaysia). This is the first study on the genetic diversity and genotype multiplicity of Plasmodium falciparum in Malaysia. Methods: Seventy-five P. falciparum isolates were genotyped by using nested-PCR of MSP-1 (block 2) and MSP-2 (block 3). Results: MSP-1 and MSP-2 allelic families were identified in 65 blood samples. RO33 was the predominant MSP-1 allelic family identified in 80.0 (52/65) of the samples while K1 family had the least frequency. Of the MSP-2 allelic families, 3D7 showed higher frequency (76.0) compared to FC27 (20.0). The multiplicity of P. falciparum infection (MOI) was 1.37 and 1.20 for MSP-1 and MSP-2, respectively. A total of seven alleles were detected; of which three MSP-1 allelic families (RO33, MAD20 and K1) were monomorphic in terms of size while MSP-2 alleles were polymorphic (two 3D7 and two FC27). Heterozygosity (HE ) was 0.57 and 0.55 for MSP-1 and MSP-2, respectively. Conclusions: The study showed that the MOI of P. falciparum is low, reflected the low intensity of malaria transmission in Pahang, Malaysia; RO33 and 3D7 were the most predominant circulating allelic families. The findings showed that P. falciparum has low allelic diversity with a high frequency of alleles. As a result, antimalarial drug efficacy trials based on MSP genotyping should be carefully interpreted.